2015
DOI: 10.1007/s11748-015-0533-z
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable sternal pins improve sternal closure stability within a small deviation

Abstract: Additional internal fixation using an HA/PLLA sternal pin significantly improved the stability of sternotomy closure in the anterior-posterior and cranial-caudal directions within a small deviation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Previously, we demonstrated that PLLA sternal pins could increase sternal stability particularly under shear stress on the sternum in biomechanical experiments using an extirpated sternum from juvenile swine (9). Koshiyama et al also biomechanically showed the efficacy of hydroxyapatite/ PLLA using an artificial sternum (21). Nevertheless, we could not identify the efficacy of the sternal pins in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Previously, we demonstrated that PLLA sternal pins could increase sternal stability particularly under shear stress on the sternum in biomechanical experiments using an extirpated sternum from juvenile swine (9). Koshiyama et al also biomechanically showed the efficacy of hydroxyapatite/ PLLA using an artificial sternum (21). Nevertheless, we could not identify the efficacy of the sternal pins in this study.…”
Section: Discussionmentioning
confidence: 59%
“…In this cohort, although the use of wire could provide good transverse reduction of the sternum after median sternotomy, it did not provide sufcient longitudinal reduction to reinforce sternal stability. Te sternal pins could nicely complement the longitudinal stability of the wire fxation [21]. Tis study also confrmed that using sternal pins for sternal fxation was positive, efective, and worth promoting, especially in infants with high-risk factors for postoperative thoracic deformities.…”
Section: Discussionmentioning
confidence: 81%
“…The cut ends are tightened until the two edges contact, and the wire stumps are buried entirely into the presternal tissue. Internal sternal fixation with absorbable sternal pins can provide additional stability with the possibility of easy re-entry [ 55 ]. Alternatively, sternal wires can be placed in a simple interrupted manner, spaced 1 to 2 cm apart.…”
Section: Closurementioning
confidence: 99%